GLP1 receptor agonists and SGLT2 inhibitors for the prevention or delay of type 2 diabetes mellitus onset: a systematic review and meta-analysis - Ghobar, Farah; Tarhini, Ali; Osman, Zeinab; Sbeih, Sergio; Ghayda, Ralph Abou; Matar, Patena; Haddad, Gaelle; Kanaan, Amjad; Eid, Assaad; Azar, Sami; Ghadieh, Hilda E.; Harb, Frederic (Frontiers in Endocrinology, 2025)
BackgroundSGLT-2 inhibitors (SGLT-2i) and GLP-1 receptor agonists (GLP-1 RA) are two widely used classes of medications in the treatment of diabetes, each demonstrating significant efficacy and adoption. These medications have shown promising results in glycemic control and offer additional health benefits such as weight loss and cardiovascular protection. The objective of our meta-analysis is to systematically assess the effectiveness of SGLT-2 inhibitors and GLP-1 receptor agonists in slowing down or preventing the progression of prediabetic patients into diabetics. By synthesizing the existing evidence, we aim to determine whether early intervention with these medications can effectively mitigate the risk of developing diabetes in prediabetic individuals. This analysis will provide critical insights into their comparative effectiveness and inform clinical decision-making for early diabetes prevention strategies.MethodsIn this meta-analysis we primarily focused on randomized control trials (RCTs) that included the use of either SGLT-2 inhibitors, GLP-1 receptor agonists, or both. The database search was conducted using PubMed, Embase, and Cochrane. Statistical analysis was performed using IBM SPSS, and the results were reported with a 95% confidence interval (CI).ResultsThe meta-analysis included 14 studies with the majority being double blinded (13/14). Effective randomization was evident from balanced baseline characteristics between treatment and control groups. Both SGLT-2 inhibitors and GLP-1 receptor agonists demonstrated significant reductions in body weight when given individually. This effect is also amplified when given as a combination therapy (SMD: -23, 95% CI: [-27.9, -18.10]). Also, fasting plasma glucose levels decreased in patients receiving treatment (SMD: -5.40, 95% CI: [-10.70, 2.24]) compared to control groups. Moreover, HbA1c levels were assessed in seven studies, where significant reductions in treatment groups were reported with a standardized mean difference of -6.95 (95% CI: [-14.24, 2.98], p-value= 0.06) for the overall effect size. Furthermore, three studies showed that SGLT-2 inhibitors reduced diabetes mellitus (DM) onset, though statistical significance was not achieved (p-value = 0.08, SMD: -2.21, CI: [-5.11, 0.69]). Finally, no significant change in fasting insulin levels was noticed with an overall SMD of -1.74 (95% CI: [-6.84, 3.37]), which was also not statistically significant (p-value: 0.55). These findings highlight the efficacy of SGLT-2 inhibitors and GLP-1 receptor agonists in reducing HbA1C, fasting blood glucose, and body weight, while also potentially delaying the progression to type 2 diabetes mellitus in prediabetic patients.ConclusionEarly medical intervention at the prediabetic stage with SGLT-2i or GLP-1 RA shows potential in modifying progression to the onset of T2DM and its adverse effects. However, more studies are needed to reliably assess which of the two yields better results and further investigate the potential of combination therapy.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024565439.